2020
DOI: 10.1186/s13071-020-04040-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxoplasma gondii oocysts in fresh vegetables and berry fruits

Abstract: Background: Toxoplasma gondii is the third most important contributor to health burden caused by food-borne illness. Ingestion of tissue cysts from undercooked meat is an important source of horizontal transmission to humans. However, there is an increasing awareness of the consumption of fresh fruit and vegetables, as a possible source for oocyst transmission, since this stage of the parasite can persist and remain infective in soil and water for long time. Herein, we outline findings related with detection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 34 publications
(56 reference statements)
1
39
0
1
Order By: Relevance
“…However, these parasites can cause severe disease, even leading to death in immunocompromised individuals [ 5 ]. According to previous reports, T. gondii can be spread by the ingestion of unsterilized meat and contaminated fruits, vegetables, and drinking water [ 6 , 7 , 8 ]. Moreover, the vertical transmission of T. gondii can cause irreversible damage to a fetus, miscarriage, and stillbirth; additionally, congenital deformities can occur [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these parasites can cause severe disease, even leading to death in immunocompromised individuals [ 5 ]. According to previous reports, T. gondii can be spread by the ingestion of unsterilized meat and contaminated fruits, vegetables, and drinking water [ 6 , 7 , 8 ]. Moreover, the vertical transmission of T. gondii can cause irreversible damage to a fetus, miscarriage, and stillbirth; additionally, congenital deformities can occur [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study revealed a high rate of T. gondii (29.6%) in leafy greens. The detection of this parasite has been reported elsewhere such as in Czech Republic 9.6% (28/292) [46] and Portugal and Spain 42.9% (14/35) [47], using molecular methods. In North Africa, only two studies have been conducted to investigate the presence of this parasite in fresh vegetables: the study performed in Egypt [15] has revealed using microscopy a contamination rate of 5.6 % (19/212), while our previous study [20] showed an overall rate of 21% (18/86), using the same qPCR.…”
Section: Discussionmentioning
confidence: 65%
“…Nonetheless, human toxoplasmosis outbreaks may be attributed to exposure to infected cats, which may indicate an important role of cat oocyst excretion on infection spreading (48,49), and homeless might be daily overexposed to environmental contamination. Another interestingly study has reported that 14/35 (40.0%) fresh vegetables and fruits collected from local producers and supermarket suppliers of Portugal and Spain were positive to T. gondii by PCR and microscopic autofluorescence (50). However, as mentioned above, homeless dietary habits of high intake of processed foods and low fresh meat, fish, vegetables and fruits may have led to lower T. gondii exposure.…”
Section: Discussionmentioning
confidence: 95%